UPAYA PENINGKATKAN TEKNIK DASAR TENDANGAN SABIT MELALUI METODE RESIPROKAL KELAS VB SDN 68 PONTIANAK - Pratama, Heru (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The problem in this research is how to increase the basic technique ability of sickle kick through reciprocal method on the students of grade V B SDN 68 Pontianak. The objective of this research is to know the effort to improve the basic technique ability of sickle kick through reciprocal method.The research method is a descriptive method with the form of classroom action research (PTK). Subject of research students VB grade SDN 68 Pontianak, amounting to 32 people. Data analysis techniques using descriptive achievement of mastery.The result of the basic technique of crescend kick was obtained for the lowest value of 59.25, the highest value 85.18, the average is 77.77. For the 1st cycle the lowest score is 74.07, the highest score is 96.29, the average is 85.18. For cycle 2 the lowest value is 85.18, the highest value is 100, averaging 92.59. The result of completeness on prasiklus is 6.26% (2 persons), cycle 1 is 50.08% (16 people) and cycle 2 is 100% (32 people). Keywords: Reciprocal, Basic Technique of Crescent Kick